Pluralitas Agama dan Kekerasan Kolektif - Muh. Yunus (UIN Maulana Malik Ibrahim Malang, 2002)
This paper describes whether there is a latent function of religion that can trigger the act of collective anarchism. It is also explored whether there is something that can move people so that they perpetrate the collective violence since the majority of Indonesian people are religious believers who all love peace. In principle, differences are not the root of violence. But man is often wrong in understanding the difference. Because the difference is a law of nature. Basically, humans need to be involved in pluralism, interacting with each other. And if in interacting to meet the peculiarities, need to be solved by way of communication (dialogue) without violence. Herein lies how sesunggulmya no difficulties that we can not solve, as long as want to communicate. Alternative roads are many that we can pass to solve life's problems. And religion offers it to us to create that peace. Dalam makalah ini dijelaskan apakah ada fungsi laten agama yang dapat memicu tindakan anarkisme kolektif. Juga ditelusuri apakah ada sesuatu yang dapat menggerakkkan orang sehingga ia melakukan kekerasan kolektif mengingat mayoritas masyarakat Indonesia adalah pemeluk agama yang semuanya cinta damai. Pada prinsipnya, berbagai perbedaan bukanlah akar terjadinya tindak kekerasan. Tetapi manusialah yang acapkali salah dalam memaknai perbedaan itu. Sebab perbedaan merupakan hukum alam. Pada dasarnya manusia perlu terlibat dalam kemajemukan, berinteraksi dengan sesamanya. Dan apabila dalam berinteraksi menemui keganjilan-keganjilan, perlu diselesaikan dengan jalan komunikasi (dialog) tanpa kekerasan. Disinilah letak betapa sesunggulmya tidak ada kesulitan yang tidak bisa kita pecahkan, asalkan mau berkomunikasi. Jalan-jalan alternatif masih banyak yang bisa kita lewati untuk menyelesaikan berbagai persoalan kehidupan. Dan agama, menawarkannya kepada kita untuk menciptakan perdamaian itu.